Intrinsic factors of job satisfaction among lecturers of Bauchi State University Gadau, Nigeria - Hassan, Abubakar Idris; Romle, Abd Rahim (ISLAMIC WORLD Network for Environmental Science and Technology (IWNEST Publisher), 2015)
The study seeks to examine the relationship between intrinsic factors and job satisfaction among the lecturers of Bauchi State University Gadau (BASUG), Nigeria.This Study uses intrinsic factors as independent variables, whereas job satisfaction as a dependent variable is based on the theoretical framework of „two factor theory‟ of Fredrick Herzberg (1959).The study employs close-ended questions adapted and adopted from the Minnesota Satisfaction Questionnaire (MSQ) and interviews were also conducted to compliment the result of the survey questions in measuring the relationship between intrinsic factors and job satisfaction among 148 academic staff of BASUG that had participated in the study. Accordingly, descriptive statistic was used in testing the data collected.The findings reveal that there is a positive and significant relationship between intrinsic factors and job satisfaction where, specifically, „responsibility‟, „work itself‟ are positively related to job satisfaction and interview responses found that staff training and library needs to be upgraded and improved in order to increase the level of job satisfaction of lecturers of Bauchi State University Gadau, Nigeria.